2022
DOI: 10.3389/fimmu.2022.957303
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the role of neutrophils in neuropsychiatric systemic lupus erythematosus: Current understanding and future directions

Abstract: Central nervous system (CNS) involvement of systemic lupus erythematosus (SLE), termed neuropsychiatric SLE (NPSLE), is a major and debilitating manifestation of the disease. While patients with SLE mostly complain of common neuropsychological symptoms such headache and mild mood disorders that may not even be technically attributed to SLE, many SLE patients present with life-threatening NPSLE syndromes such as cerebrovascular disease, seizures and psychosis that are equally challenging in terms of early diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 188 publications
0
4
0
Order By: Relevance
“…The study of neutrophils, especially neutrophil heterogeneity, is of great momentousness in the field of cardiovascular and cerebrovascular diseases. 201 , 202 , 203 The normal‐density neutrophils (NDNs) and LDN subpopulations in the peripheral blood of patients with hypertension‐associated chronic inflammation exhibited higher levels of Na + influx and ROS, along with lower levels of apoptosis and stronger proinflammatory ability, thereby promoting the chronic inflammatory response associated with hypertension. 204 Some research teams identified that Ly6G + SiglecF + (Myc + NFϰB + ) neutrophils served as proinflammatory cells in the progression of myocardial infarction (MI).…”
Section: Neutrophil Heterogeneity In Diseasesmentioning
confidence: 99%
“…The study of neutrophils, especially neutrophil heterogeneity, is of great momentousness in the field of cardiovascular and cerebrovascular diseases. 201 , 202 , 203 The normal‐density neutrophils (NDNs) and LDN subpopulations in the peripheral blood of patients with hypertension‐associated chronic inflammation exhibited higher levels of Na + influx and ROS, along with lower levels of apoptosis and stronger proinflammatory ability, thereby promoting the chronic inflammatory response associated with hypertension. 204 Some research teams identified that Ly6G + SiglecF + (Myc + NFϰB + ) neutrophils served as proinflammatory cells in the progression of myocardial infarction (MI).…”
Section: Neutrophil Heterogeneity In Diseasesmentioning
confidence: 99%
“…Systemic tissue injury is a major characteristic of SLE [50], and neutrophils are involved in damage caused in the kidneys [15], skin [15], placenta [51 ▪ ], and nervous system [52 ▪ ]. Mechanistically, neutrophils recruited by local chemokines and immune complexes can produce tissue-damaging molecules such as granzymes and reactive oxygen species (ROS) [10 ▪ ].…”
Section: Neutrophils Mediate Multi-organ Damage In Systemic Lupus Ery...mentioning
confidence: 99%
“…Polymorphonuclear cells (neutrophils) are the most abundant circulating immune cell in humans, representing 50–70% of all leukocytes [ 1 , 2 ], are an important component of the innate immune system [ 3 ], and are part of the first line of defense against microorganisms [ 4 ]. Neutrophils also have a role in tissue homeostasis, but aberrant activation and persistence can contribute to inflammation and the progression of some disease conditions [ 3 ], including acute respiratory distress syndrome (ARDS) [ 5 ], rheumatoid arthritis (RA) [ 6 ], and many other disorders [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%